Урахувуання залежності часу добігання води від її рівня і витрат - Ostapenko, V. V.; Ostapenko, O. S.; Finin, G. S.; Jakovleva, A. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A model of water motion in irrigation system channels that takes into account dependence of running time on water expenditure level is considered. Methods of solving of irrigation optimal control system are described.